Preparation of Financial Statement Using the Microsoft Excel on PT Dehong Paper Industry - Dwi Fajar Noviato; Nanik Lestari (Journal of Applied Accounting and Taxation, 2022)
This research aims to prepare financial statements using Microsoft Excel in the PT Dehong Paper Industry. Data collection techniques are observation, interviews, and documentation. The data analysis method used is the descriptive method. The research concludes that by using Microsoft Excel, the information obtained can be real-time, synchronous, and interactive. It can be easily streamlined by following the flow of steps using a simple excel formula.